1985
DOI: 10.1037/0021-843x.94.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for real and hypothetical events: Their relation to self-esteem and depression.

Abstract: The association between attributional style, self-esteem, depressive symptoms, and general distress was examined to test hypotheses derived from a learned helplessness model and Weiner's (1979) attributional model of motivation. After answering questionnaires on depression, general distress, and self-esteem, 178 male and female undergraduate students were asked to make causal attributional ratings about 12 hypothetical events; 151 subjects also were asked to make diary ratings on 14 real events. Results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…In a nonclinical sample, Zautra et al (1985) examined the association between attributional style, self-esteem, depressive symptoms, and general distress and found that internal attributions for positive outcomes were primarily associated with high self-esteem. Only internal stable attributions for negative outcomes were related to depressive symptoms.…”
Section: Self-esteemmentioning
confidence: 99%
“…In a nonclinical sample, Zautra et al (1985) examined the association between attributional style, self-esteem, depressive symptoms, and general distress and found that internal attributions for positive outcomes were primarily associated with high self-esteem. Only internal stable attributions for negative outcomes were related to depressive symptoms.…”
Section: Self-esteemmentioning
confidence: 99%
“…For example, Needles and Abramson (1990) stated, ".even among those at risk for hopelessness depression, there may be a subset who have the hypothesized enhancing style for positive events and who thereby may be better able to recover." Indeed, studies reveal that negative and enhancing cognitive styles are either statistically unrelated (e.g., Voelz et al, 2003) or weakly positively correlated (correlations ranging from 0.01 to 0.40 in prior studies) and exhibit different patterns of associations with depressive symptoms (e.g., Sweeney, Anderson, & Bailey, 1986;Voelz et al, 2003;Zautra, Guenther, & Chartier, 1985).…”
Section: Introductionmentioning
confidence: 97%
“…Most individuals take credit for their successes and blame external factors for their failures (Cohen, van der Bout, Vliet, & Kmmer, 1989;Kuiper, 1978;Rizley, 1978;Zautra, Guenther, & Chartier, 1985). Low self-esteem individuals, however, are less likely to make these self-serving and self-protective attributions, and tend to make internal attributions for failure (Fitch, 1970;Ickes & Layden, 1978;Tennen & Henberger, 1987).…”
Section: Self-esteem and Self-regulationmentioning
confidence: 99%